Kopenske vode v geografskem okolju - Vovk Korže, Ana (Geografski obzornik, 2003)
The inland waters are only a (small) part of the hydrosphere, but have an important meaning for the human beings. Water is an essential natural resource, the quality of life depends on its quantity, quality and presence. Therefore one should establish suitable attitude towards water
Keywords: hidrologija; hidrogeografija; kopno; sladke vode; vodni viri